Synchronizacja czy dezintegracja światowego cyklu koniunkturalnego? - Polszakiewicz, Barbara (Synchronisation or desintegration of a world business cycle?, 2006)
This article contains an attempt at an identification of a world business cycle as a WW II phenomenon that is also present in today’s economy. The recurrence of overproduction cycles has been adopted as a synchronisation criterion. The economies of the USA and Germany have been analysed in detail. As far as other economies are concerned, only some quite synthetic suggestions have been made.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 173-183